Inequality and potential: A sociological analysis of the role of local communities in the tourism economy around Lake Lut Tawar - Mallia Hartani; Suci Wahyu Fajriani; Kurnia Asni Sari; Lisya Septiani Putri (Privietlab, 2025)
This study examines the unequal distribution of economic benefits and potential for local community development in the Lut Tawar Lake tourist area, Central Aceh Regency, using Anthony Giddens' structuration theory as a single analytical framework. A qualitative approach was used through literature review, field observations, and semi-structured interviews. The results indicate that the cultural and natural potential of the local community has not been optimally utilized due to the dominance of external capital, policies that are not yet in favor, and limited community capacity. Structure-agency analysis reveals that the imbalance between policies, regulations, and structural support with the initiatives and capabilities of local actors is the main source of inequality. The proposed strategies include strengthening agencies through training, affirmative regulation, and strengthening market networks to create a balance between structure and agency.